Evidências de interações medicamentosas entre psicofármacos a partir de notificações de suspeitas de reações adversas - Soares Neto, Julino Assunção Rodrigues [UNIFESP] (2016)
Introduction: Drug interactions (DIs) might result in adverse drug reactions (ADRs) that entail high mortality rates and have a significant impact on health systems. Objective: To search for evidence of DIs between psychotropic medications that have clinical relevance by analyzing notifications of suspected adverse drug reactions (SADRs). Method: Using notifications of SADRs, we described and analyzed reports of adverse events and the drugs mentioned. Thereafter we selected the drug most often notified and with a higher number of serious events, and then the interactions with that drug. We used information in the literature and from the medicine labels for the classification and discussion of the SADRs and DIs, their predictability, related mechanisms and clinical relevance. Results: We analyzed 411 notifications, out of which 36% (n=149) of the events were classified as serious. The antidepressants were responsible for 50% (n=204) of the SADRs notified and for 40% (n=59) of the events classified as serious; the pharmacologic class most often notified was that of selective serotonin reuptake inhibitors. The most frequent outcome among the serious events was hospitalization (46%). Venlafaxine (VEN) was the most notified drug (10% out of 411 notifications) and the one with the highest number of serious events (8% out of 149 cases). There were reports of 21 drugs used concomitantly with VEN, being benzodiazepines (n=10) the most co-notified pharmacologic class, with clonazepam as the most co-notified with VEN. The clinical manifestations were grouped into diseases of the nervous system (55%), gastrointestinal disorders (41%) and psychiatric disorders (28%), among which therapeutic failure (n=4) was the most often notified. The most serious events with VEN were an abortion; a premature birth followed by the death of the newborn; a cerebral vascular accident; a cerebral vascular accident with recurrent depression and death. Nortriptyline, clomipramine, bupropion and buspirone were classified as risk of serious DI when associated with VEN, while mirtazapine, naratriptan, lithium and propranolol were classified as moderate. Discussion: Most of the clinical manifestations/adverse events described in the notifications regarding VEN are consistent with the sources we researched. Some of them, however, are not described in the medicine labels, or are described as requiring further studies. Moreover, the labels researched do not directly mention the predictability of adverse DIs of VEN with the other drugs co-notified, with the exception of mirtazapine. Rather, they alert on the risk of adverse DIs considering some therapeutic classes or pharmacodynamic and pharmacokinetic mechanisms. VEN has one of the highest indices of toxicity among antidepressants, and there are publications on the risk of ADRs and DIs, such risks are not described in the labels. We also observed differences in the data between the sources consulted and conflict of interest in the publications. Mirtazapine presented the highest agreement among the sources researched as to the risk of DI, but such risk was not described in the label of VEN. We did not find direct evidence of a possible DI between clonazepam and VEN, although both share the same biotransformation pathway. The literature researched described the serotoninergic syndrome and some cases of an increase in the QT interval as the most common adverse effects resulting from a DI with VEM. The possible mechanism of DI with VEM, most frequently described in the literature, would be the inhibition of cytochrome P-450 (CYP), also described as having possible addictive effects. Conclusions: The analysis of the SADRs notifications, according to the literature, suggests that the concomitant use of VEN with some drugs is related to little known and serious DIs associated with changes in the activity of the CYP2D6 and 3A4. The present study points to the need of investigating the DI between VEN and clonazepam, in addition to reviewing some data presented in the label of VEN and monitoring measures, especially for patients with renal and hepatic insufficiency, pregnant women, polymedicated individuals and those with a slow biotransformer phenotype.